DEVELOPMENT OF AUTONOMY FOR HEALTHCARE SURFACE DISINFECTION ROBOTS - Tito Kurniawan, Irfan
Surface disinfection plays a major role in preventing healthcare-associated infections, especially in the COVID-19 pandemic. However, the conventional surface disinfection process poses a risk of infection to the individual doing the task. The tedious nature of the task only adds to the inconsistency of the disinfection result. Ultraviolet-C irradiation is an effective method of contactless surface disinfection. However, as ultraviolet-C irradiation is harmful to humans, the operator of the irradiation device has to suffer both the risk of infection and radiation. Autonomous robots are a prime candidate for an ultraviolet-C lamp carrier. Due to their autonomy, disinfection can be carried without the need for human intervention, enabling a safe disinfection process without neither the risk of infection nor radiation. This research develops an autonomy software for healthcare surface disinfection robots. The autonomy itself is decomposed into three modular subsystems: Augmented Monte Carlo Localization based localization, Rapidly Exploring Random Tree* based path planning, and Spanning Tree Coverage based coverage path planning. The software is then tested in a simulated environment. The test results show that the developed software enables the sterilization of 53.82–77.55% out of all surfaces in the environment in 11.57–20.56 seconds per square meters of the surface area of the environment.